Background to and issues in designing a system for the collection of agricultural statistics in Uganda - Muwanga-Zake, E. S. K. (International Food Policy Research Institute, 2009)
This paper provides a background on past and current efforts to generate national agricultural production estimates for Uganda across a range of institutions. Several sets of issues related to the design of a sustainable and spatially disaggregated annual agricultural production estimates system for Uganda are then considered, including technical and geographical considerations, administrative modalities, and resource challenges.